Pengembangan LKPD Pembelajaran Tematik Pada Subtema Tumbuhan Sahabatku Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VI SD Negeri 56 Maluku Tengah - Yati Tuasamu; Nur N; Safarin Zurimi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The learning process in the 2013 curriculum is still difficult to implement so that it has an unfavorable impact on student learning outcomes. For this reason, learning tools are needed that can provide meaningful learning activities and can support a scientific approach to improve student learning outcomes. This study aims to determine the increase in learning outcomes of class VI students at SD Negeri 56 Central Maluku through the development of thematic learning worksheets on the sub-theme My Best Friend Plants. This research was conducted from October to November 2022 at SD Negeri 56 Central Maluku. The research object was the developed LKPD, while the research subjects were 19 students in class VI at SD Negeri 56 Central Maluku. The LKPD development method for adapting the 4D model consists of 1) defining, 2) planning, 3) developing, and 4) distributing LKPD. The results obtained by the developed LKPD are categorized as valid and suitable for use as teaching materials based on the opinions of 2 expert validators (academics). The learning outcomes of students using the developed LKPD have increased where the affective and psychomotor aspects are in good and very good qualifications while the cognitive aspects are in sufficient, good, and very good qualifications. So that it can be concluded that the LKPD developed on the thematic learning of the My Best Friend's Plants sub-theme is suitable for use as teaching material because it can improve student learning outcomes above the KKM standard (75).Â